Gulo gulo gulo Linnaeus 1758 - Fourvel, Jean-Baptiste; Fosse, Philippe; Fernandez, Philippe; Antoine, Pierre-Olivier (Zenodo, 2015)
Gulo gulo Linnaeus, 1758 MATERIAL EXAMINED. — NISP =9; MNI =6. 1842 sample: 1 left tibia. 1989-1992 sample: 1 left P3; 1 left humerus; 1 right ulna; 1 left ulna; 2 right innominates; 1 left innominate; 1 right femur. The Pleistocene wolverine was recorded for the first time in France at Fouvent (Gervais 1870). This inhabitant of modern arctic areas (Pastichniak-Arts & Larivière 1995) was a conspicuous element of Last Glacial Maximum faunas in Europe (Kurtén 1968). Although it is found in many sites (review in Döppes 2001), detailed descriptions of both cranial and postcranial elements are quite rare (e.g., Villereversure in Martin1968; Jaurens in Mallye & Guérin 2002).Nine remains from Fouvent (representing six individuals) have been attributed to the wolverine. Seven remains brought to light some additional morphometrical features of the knowledge of this species (Table 4). For example the P3 (F11.B.223) shows a fairly massive crown which is made of a single antero-posterior cusp crossed by a protruding edge. Moreover, a cingulum is strongly developed at the base of the lingual side. The dimensions of this tooth compared to large recent and fossil mustelids (Wolverine and Badger) permit us to identify it as G. gulo (Fig. 5). Furthermore, morphometrical data allow us to exclude the Badger Meles meles Linnaeus, 1758. Finally the specimen of Fouvent has relatively small dimensions compared to the Pleistocene gluttons but fits well among the greatest living representatives of G. gulo . mm. * , juvenile; sin , left; dext , right. Other abbreviations: see text. Published as part of Fourvel, Jean-Baptiste, Fosse, Philippe, Fernandez, Philippe & Antoine, Pierre-Olivier, 2015, Large mammals of Fouvent-Saint-Andoche (Haute-Saône, France): a glimpse into a Late Pleistocene hyena den, pp. 237-266 in Geodiversitas 37 (2) on pages 244-246, DOI:10.5252/g2015n2a5, http://zenodo.org/record/4535125